2018
DOI: 10.1093/emph/eoy027
|View full text |Cite
|
Sign up to set email alerts
|

Influenza, evolution, and the next pandemic

Abstract: Mortality rates in influenza appear to have been shaped by evolution. During the 1918 pandemic, mortality rates were lower in children compared with adults. This mortality difference occurs in a wide variety of infectious diseases. It has been replicated in mice and might be due to greater tolerance of infection, not greater resistance. Importantly, combination treatment with inexpensive and widely available generic drugs (e.g. statins and angiotensin receptor blockers) might change the damaging host response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 89 publications
1
11
0
1
Order By: Relevance
“…In view of these overall considerations, we can speculate that SARS-CoV-2 infection may not have spread in a fully susceptible population. This hypothesis may be also confirmed by a previous study by FEDSON [13], which reported that the different age-related mortality during the 1918 influenza pandemic could be related to @ERSpublications Other reasons, rather than absence of prior immunity, could play a crucial role in the coronavirus dilemma that surrounds children https://bit.ly/36BzTaD previous exposures to the H1N1-like viruses, suggesting a fundamental role of "antigenic imprinting" on individual response.…”
Section: From the Authorssupporting
confidence: 69%
“…In view of these overall considerations, we can speculate that SARS-CoV-2 infection may not have spread in a fully susceptible population. This hypothesis may be also confirmed by a previous study by FEDSON [13], which reported that the different age-related mortality during the 1918 influenza pandemic could be related to @ERSpublications Other reasons, rather than absence of prior immunity, could play a crucial role in the coronavirus dilemma that surrounds children https://bit.ly/36BzTaD previous exposures to the H1N1-like viruses, suggesting a fundamental role of "antigenic imprinting" on individual response.…”
Section: From the Authorssupporting
confidence: 69%
“…Modern analysts invoke other possibilities, as will be discussed below [ 11 ]. Later in this volume David Fedson considers age-related influenza mortality rates in detail, with evolutionary implications and suggestions for public health response [ 12 ].…”
Section: History Of the Pandemic (I)mentioning
confidence: 99%
“…Influenza A viruses (IAVs) are characterized by a particulate morphology with the size at 80-120 nm in diameter, consisting of segmented RNA, a typical glycoprotein-studded lipid envelope overlying a matrix protein 1 (M1). IAVs infect a broad range of species, including wild birds, poultry, and humans, resulting in annual flu epidemics and global pandemics1. Although various vaccines have been developed against IAVs, antigenic shift and drift accelerate the diversity and emergence of novel stains, rendering timely vaccine development a considerable challenge2.…”
Section: Introductionmentioning
confidence: 99%